2019
DOI: 10.1186/s12902-019-0341-z
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported hypoglycemia in adult diabetic patients in East Gojjam, Northwest Ethiopia: institution based cross-sectional study

Abstract: BackgroundHypoglycemia presents a barrier to optimum diabetes management and it is related to a negative impact on health-related quality of life, healthcare resource use, and work productivity. Despite the fact that the magnitude of hypoglycemia and factors associated with hypoglycemia in diabetic population were demonstrated in clinical trial settings; there is no adequate evidence concerning to the problem in real-world settings, in particular in the study area. The aim of the study was to assess the magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…Besides this, it could be due to the fact that those who are treated for a long duration may have become fatigued and caught napping on the techniques to administer insulin by themselves. This finding was supported by studies done in Ethiopia (5,22).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Besides this, it could be due to the fact that those who are treated for a long duration may have become fatigued and caught napping on the techniques to administer insulin by themselves. This finding was supported by studies done in Ethiopia (5,22).…”
Section: Discussionsupporting
confidence: 80%
“…Diabetes mellitus significantly contributes to the global health burden in the 21 st century (1). Achieving good glycemic control is a valuable goal for people with diabetes (2); however, hypoglycemia is the greatest challenge to achieving tight glycemic control (3)(4)(5)(6)(7), which results in declined drug compliance, cardiovascular events, and even mortality (3). It is also related to a negative impact on health-related quality of life, healthcare resource use, and work productivity (5).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include failure to seek help, unavailability of regular screening programmes for patients suspected of having T1DM, inability to make a formal diagnosis, inadequate and inappropriate care exacerbated by the lack of equipment, facilities and professionals, e.g. Ghana currently has less than fifteen endocrinologists, poor knowledge among patients and parents, frequent episodes of hypoglycaemia exacerbated by a lack of insulin and the cost of insulin as well as monitoring sticks and syringes, poor storage of insulin, poor adherence to treatments and poor eating habits as well as cultural aspects of care (1,6,20,24,43,44,62,63,80,(95)(96)(97)(98)(99)(100)(101)(102)(103)(104). The WHO in 2015 found that in SSA only 51% of the countries had metformin routinely available and only 40% had insulin readily available, well below the 80% target (1, 105).…”
Section: Country Epidemiologymentioning
confidence: 99%